Rupee Devaluation, its Causes and Impact on Indian Economy: Analyzing the Causes and Impact of Rupee Devaluation on the Indian Economy (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The devaluation of Indian currency has positive and negative impact on Indian economy. Devaluation means officially lowering the value of currency in terms of foreign exchange. The devaluation of currency is done by government. The rupee is devalued first in 1966 by 57 from Rs. 4.76 to 7.50 against US dollar. In the year 1991, the rupee was again devalued by 19.5 from Rs.20.5 to Rs.24.5 against the US dollar. In this paper, an attempt is made to review the probable reasons for the devaluation of the rupee and analyses the impact of currency devaluation on the various sector of the country. For this required data is collected from various Journals and websites. Pros and cons of currency devaluation are studied as boon and bane for the economic growth.